(untitled) (Advancements in Homeopathic Research, 2025)
The International Year of Quantum Science and Technology (IYQ) 2025 is a global initiative celebrating 100 years since the development of quantum mechanics1. This year-long event aims to raise awareness about the importance of quantum science and its applications2. There is optimism about huge potential for quantum computing in areas such as chemistry, biochemistry and materials science — significantly advancing fields such as healthcare and manufacturing, especially when used to refine and improve artificial intelligence models3. Quantum science and technology have the potential to revolutionize various fields, including medicine. Homeopathy is well represented in Indian landscape of public health, being a close second among the AYUSH (Ayurveda, Yoga and Naturopathy, Unani, Siddha and Homeopathy) services. India offers a range of medical treatment modalities to its population in a cafeteria approach. Ministry of Ayush aims at providing its people with wider access to homeopathy. Homeopathy wellness centres comprise 31% of the total for AYUSH. Seven out of 10 diseases recognised as a national health burden are in the category of most commonly reported diseases at the homeopathy wellness centres4.